Diseño editorial ilustrado referente de la fauna de Parque Nacional Cotopaxi - Fernández Toapanta, María Cristina (2017)
The research project helped to solve the problem about the lack of visual information of the species with high vulnerability found in Cotopaxi National Park. It was identified that the animals in endangered according to the Ministerio del Ambiente are: whitetail deer, spectacled bear, paramo wolf, cervicabra, opossum, and Andean weasel. The most important birds are: falcon, owl, Andean gull, curiquingue, paramo partridge, red-backed hawk, Andean condor and warm-blooded hummingbird called Estrella de los Andes. It was considered a total of 14 species that must be shown. It was raised using the editorial design in conjunction with the graphic illustration to identify these animals and in turn build an editorial product. For the research theoretical framework was obtained about the Cotopaxi National Park as its tourism resources and native fauna, with predominant content this was reflected in this national reserve. Qualitative instruments was applied (interviews) and quantitative (surveys) which will determine and disclose information by experts in graphic design that provided experiences and parameters for the realization of the project. The design of the book and layout and layout that followed a design process: from page layout sketches on paper, the selection of the grid, the digital layout, the stain marks, and the construction of the editorial style. In the final stage of the project was the Hans Gugelot´s design methodology which served for the realization of the product in stages: by means of selecting the information, research, design, decision, production and testing. As a conclusion, it was obtained a visual, aesthetic and communicative this reserve of Ecuador.